The Relationship of Cash Conversion Cycle with Firm Size and Profitability: A Survey on Manufacturing Companies in Sri Lanka - Pratheepkanth, P. (South Eastern University of Sri Lanka, 2011)
In this paper investigate the relation between the length of the CCC and the size of the firms, and the length of the CCC and profitability. The researcher collected data of this study from the financial statements of the Companies listed on the CSE for the year 2009. The researcher utilized ANOVA and correlation analyses for empirical investigation. The major findings of the study are as follows. The lowest mean value of the CCC is found in the Manufacturing Companies, with an average of 3S.99 days, and the highest mean value of the CCC is found in the textile Companies, with an average of 163.33 days. There is a significant negative correlation between the CCC and the variables; the firm size and the profitability. The findings of this paper are based on a study conducted on the CSE. Hence, the results are not generaliseabIe to non-listed companies.
Keywords: Cash Conversion Cycle; Firm Size; Profitability; Sri Lanka